Implementasi Integrated Marketing Communication pada Bengkel Jepang Motor - Andriati, Salsabila; Teguh, Monika (Jurnal Interaksi: Jurnal Ilmu Komunikasi, 2025)
The automotive industry in Indonesia plays a crucial role in the national economy, making a significant contribution to gross domestic product (GDP), creating employment opportunities and attracting foreign investment. In 2022, the Indonesian automotive industry will experience rapid growth with car sales reaching 1.05 million units and car production increasing to 1.47 million units. However, this sector is facing environmental challenges due to a spike in exhaust emissions and a shift in consumer preferences who are increasingly dependent on digital platforms. Japan Motor Workshop in Sidoarjo, East Java, is a successful example with turnover growth of 20% in 2023, reaching IDR 5 billion. This success is driven by the effective implementation of Integrated Marketing Communication (IMC) strategies. This research uses a quasi-qualitative method to analyze the implementation of IMC at the Japan Motor Workshop. Data was collected through interviews with business owners, customers, and academic experts, as well as studying related documentation. This analysis aims to identify how IMC strategies are implemented and their impact on brand image and customer loyalty. The research results show that the implementation of IMC at the Japan Motor Workshop has succeeded in increasing message consistency and strengthening the brand image. Through the use of various communication channels, the workshop is able to reach a wider audience and increase customer engagement. The implementation of IMC elements such as advertising, sales promotions, and public relations has proven to be effective in building customer loyalty. The discussion of these findings highlights the importance of IMC strategies in facing challenges in the growing automotive industry. By adapting to digital technology and developing environmentally friendly vehicles, the workshop not only contributes to economic growth but also provides solutions to environmental challenges.